Marketing Outlets Identification and Distribution Hybrid Corn Pioneer in PT. DuPont Indonesia - Muhammad Fatikhillah; Bambang Susilo; Rini Yulianingsih (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2015)
The marketing is a whole system of business activities aimed at planning, determine the price of, promoting and distributes goods and services which satisfies the need both to the existing and potential buyers. Marketing management from PT. Dupont Indonesia can be categorized systematic or in accordance with study theory which exists because the continued use of channel management marketing through distribution channels that were on the sphere of work space PT. Dupont Indonesia. The strategy used in company PT. Dupont Indonesia system is using a push strategy and pull strategy that keep seeing market segmentation existing. A groove distribution hybrid corn seeds Pioneer started from the factory Pioneer in Malang. A dealer will do reservations seeds and be sent back from the factory to the warehouse central each a dealer. A dealer having stall a lock (R1) in all the region that is on Sub District Nortern of East Java (NEJ) it also functions as a store of the hybrid corn seeds Pioneer. Kiosks R1 (Retail 1) will distribute seeds hybrid corn Pioneer to the kiosks R2 (Retail 2). Farmers can get hybrid corn seeds Pioneer from the dealer , key kiosks, MAP (Mitra Andalan Pioneer) or kiosks R2 (Retail 2).   Key Word : PT. Dupont Indonesia, Hybrid, Dealer, Retail 1 dan 2, Sub District Nortern of East Java (NEJ), dan MAP (Mitra Andalan Pioneer)